Financial frictions, financial shocks and labour market fluctuations in Canada - Yahong Zhang (Bank of Canada, 2011)
What are the effects of financial market imperfections on unemployment and vacancies in Canada? The author estimates the model of Zhang (2011) - a standard monetary dynamic stochastic general-equilibrium model augmented with explicit financial and labour market frictions - with Canadian data for the period 1984Q2-2010Q4, and uses it to examine the importance of financial shocks on labour market fluctuations in Canada. She finds that the estimated value of the elasticity of external finance, the key parameter capturing financial frictions, is much higher than the value suggested in the literature. This gives rise to a larger amplification effect from the financial accelerator mechanism, which helps the model generate a more volatile labour market. The author finds that the model accounts well for the cyclical behaviour of unemployment and vacancies observed in the data. She also finds that financial shocks are one of the main sources of fluctuations in the Canadian labour market. Overall, financial shocks contribute about 30 per cent of the fluctuations in unemployment and vacancies for the Canadian economy.
Keywords: E32; E44; J6; 330; Economic models; Financial markets; Labour markets